FONEMIK BAHASA DAYAK KETUNGAU SESAT - ., Hotma Simanjuntak (Jurnal Pembelajaran Prospektif, 2018)
This phonemic of the Ketungau Sesat Dayak Language study is a continuation of two phonemic studies that have been completed, namely the Dayak Kanayatn phonemic and Ulu Sakado Dayak Language Phonemic. The findings based on the theory of Distinctive Features of the three phonemic studies of the Dayak languages show the existence of similarities in the number and types of phonemes, allophones, series, and syllables. On the other hand there are phonemic differences between the three languages: there are languages that are rich in diphthong, but there are languages that do not have diphthongs. In addition, all three languages do not have a cluster group, and do not have prosodic phonemes. The results of the study Ketungau Sesat Dayak Language showed the existence of vowel, consonant, semivocal and diphthong phonemes. All vowels Ketungau Sesat Dayak Language are in groups or vowel series. It is also evident that inner phonemes Ketungau Sesat Dayak Language are symmetrical, namely / p, b, m /; / t, d, n /; /Ã, j, Ã± /; / k, g, Å‹ /. The Ketungau Sesat Dayak Language syllable consists of four types: minimum syllabic ; onset and peak; peak and coda; and onset peak and coda. Therefore, to perfect this research, the next research is expected to be able to find phonemic data from the use of modern Ketungau Sesat Dayak Language, namely the Dayak language used in scientific forums, which discusses various aspects of life.